Improving Studentsâ Reading Comprehension Through Cloze Test Method - Saleh, Yuwin R. Saleh R. (IAIN Sultan Amai Gorontalo, 2015)
This research was a classroom action research conducted at the second semester students of English Study Program IAIN Sultan Amai Gorontalo, academic year 2012/2013. This research was done into 2 cycles. The chief aim of this research was to investigate whether cloze test method can improve the studentsâ reading comprehension. The data of this research gained from observation sheet of lecturerâs activities, observation sheet of studentsâ learning activities, observation sheet of retelling, and test to know studentsâ reading comprehension in answering questions and retelling the reading texts. From analysis data of cycle 1 to cycle 2 it shown that the studentsâ reading comprehension in answering questions achieved 77.78% while studentsâ reading comprehension in retelling achieved 83,33%. It means that the action hypothesis the cloze test method can improve the studentsâ reading comprehension at the second semester of English Study Program of IAIN Sultan Amai Gorontalo of academic year 2013/2014 has proved and can be accepted.